The Determinant of Foreign Direct Investment in Indonesia - Muhammad Ghazi (Jurnal Bisnis dan Akuntansi, 2021)
This research is trying to figure out the determinant of foreign direct investment in Indonesia from the year 2011 to 2016. The researcher are going to include variable such as degree of openness, gross domestic product growth, gross domestic product per capita, and so on, as the variable that is deemed to be able to attract foreign direct investment. The data used for this research are collected from provinces across Indonesia. Hence, a panel data will be used in this research. In addition, a fixed effect regression method is employed in this research, as it is currently deemed as the most appropriate statistical analysis technique for this research. The result of this research is that the variable degree of openness is the only variable that is significant on affecting foreign direct investment, which has a negative value. Thus, this research concludes that the characteristic of inward foreign direct investment to Indonesia is tariff-jumping.